Production of calcined eggshell: Process description and economic analysis - Lim Jun Jie; Sethupathi Sumathi; Mohd Ismail Nor Ismaliza (E3S Web of Conferences)
Adsorbents derived from eggshell (ES) have been proven to be effective for a variety of pollutants including organic and inorganic pollutants from different types of wastewater. Calcined eggshell (CES) had demonstrated a significant performance in which are on par with or even exceeds the commercially available adsorbents for phosphorus removal or recovery. This study aims to develop the process flow diagram for large scale production of CES with an overall economic analysis. A process flow diagram was developed starting from the transportation to storage of final product, CES. Calculation of process parameters were based on 1,000kg ES/day with 50% yield after the calcination process, generating about 475 kg CES/day. The total production cost was RM542,809.82 for producing 148, 675 kg of CES per annum. Based on these values, the cost of CES production per kg was estimated as RM3.58 or 0.76 USD. There is a great potential for CES in the future for the remediation of water and air pollutants.